2018
DOI: 10.1007/s40618-018-0881-5
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation of genes regulating appetite and prediction of weight loss after bariatric surgery in obese individuals

Abstract: In severely obese subjects, the degree of DNAmeth of some genes affecting obesity and related conditions does not work as predictor of successful response to RYGB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 42 publications
0
5
0
2
Order By: Relevance
“…Nowadays researches are made in the identification of specific biomarkers predicting the response to RYGB procedure [42]. As an example, a previous study by our research group identified difference between the baseline SERPINE-1 methylation of the individual who lost more or less weight after bariatric surgery [43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays researches are made in the identification of specific biomarkers predicting the response to RYGB procedure [42]. As an example, a previous study by our research group identified difference between the baseline SERPINE-1 methylation of the individual who lost more or less weight after bariatric surgery [43].…”
Section: Discussionmentioning
confidence: 99%
“…As an example, a previous study by our research group identified difference between the baseline SERPINE-1 methylation of the individual who lost more or less weight after bariatric surgery [43]. On the other hand, other authors recently found no association between the methylation level of food intake-related genes and the response to surgery [42]. In line of this, linear regression analysis between the baseline methylation levels and the phenotypic markers were performed and showed association of the MYOM1 , TMEM48 , and HSF2BP methylation levels with the anthropometric and metabolic parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Surgery-induced weight loss has also been associated with remodeling of sperm DNA methylation, notably at genetic locations implicated in the central control of appetite [31]. However, Coppedè et al [32] demonstrated that DNA methylation of genes encoding for molecules regulating appetite, food intake, or obesity does not successfully predict weight loss following Roux-en-Y gastric bypass.…”
Section: Epigenetics and Bariatric Surgerymentioning
confidence: 99%
“…Estudos prévios evidenciaram redução média de 26,4 cm (CHIAPPETTA et al, 2018) (COPPEDÈ et al, 2019;LIASKOS et al, 2018).…”
Section: Análise De Bioinformáticaunclassified
“…Sugere-se que a perda de peso sofra uma maior influência da ingestão alimentar do que da metilação do gene POMC.A literatura tem mostrado que a principal preocupação com relação aos estudos nessa área refere-se à escolha dos sítios CpGs em regiões relevantes no gene(LI et al, 2016), no entanto nosso estudo mostrou que mesmo níveis de metilação em regiões não promotoras apresentaram efeito na expressão gênica e também nas variáveis clínicas. E, de acordo comCoppedè et al (2019), os dados existentes até o presente momento não permitem afirmar que os níveis de metilação estejam envolvidos na regulação do apetite e saciedade. Mais estudos precisam ser conduzidos para elucidar o papel da metilação do DNA nos genes de apetite e saciedade e os desfechos relacionados a DGYR.…”
unclassified